Argyria mimicking a blue nevis: dermoscopy features* - Enei, Maria Leonor (Sociedade Brasileira de Dermatologia, 2013)

(untitled)
Argyria is a rare disease caused by prolonged skin contact with silver. Localized cases have been described regarding the use of topical medications, and trauma with objects containing this metal such as acupuncture needles and jewelry. Clinically, a macule or a patch, round or oval, appears in the infected area, with a characteristic bluey-gray color. To our knowledge this is the first time that this clinical condition has been described through the use of dermoscopy.